Control of speed-strength load in training of skiers-racers based on the application of tools - Vasilyeva V.S. ,; Dorozhko A.S. ,; Karaseva T.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to experimentally substantiate the use of feedback tools in the operational control of speed-strength loads in the training of highly qualified ski racers. Methods and structure of the study. The experiment involved ski racers (n=4; MS; 24.5±3.8 years). During 15 training sessions, athletes performed interval exercises using a ski ergometer with regulation of the intensity of physical activity and monitoring of the bioelectric activity of the triceps brachii and latissimus dorsi muscles. The duration of the approaches was 30 seconds with rest pauses of 180 seconds. The intensity of the load was set within 80-85% of the maximum power shown in the test exercise on the ski ergometer. The number of approaches was determined based on muscle contractility. To assess the effectiveness of training, athletes were asked to undergo two tests with a stepwise increasing load on a roller ski treadmill. The test result was assessed by the number of load stages performed, the frequency of movements, the impulse of the driving force of pushing off with ski poles and the reactivity coefficient of the driving force. Results and conclusions. The performance of athletes increased due to greater manifestation of speed-strength abilities, as indicated by an increase in impulse indicators and the reactivity coefficient of the driving force. The proposed method of managing the training load using tools can be considered as recommendations for increasing the efficiency of the training process of highly qualified cross-country skiers. The basis of the load management technique using a ski ergometer is: the number of approaches is no more than 10; rest between sets 180 seconds; stopping criterion is a decrease in the power and magnitude of muscle bioelectric activity by more than 10% within 15 seconds.